Productivity gap and comparative advantage of BADC Boro rice seed production in Bangladesh - Mia, M S; Uddin, M T; Kabir, H; Miah , M A M; Salam, M A S (SAARC Journal of Agriculture, 2023)
Productivity gap in this study is the difference between the productivity of BADC Boro seed and non-BADC Boro seed at the farm level. Again, the economic competitiveness of hybrid Boro seed produced by Bangladesh Agricultural Development Corporation (BADC) is measured through Domestic Resource Cost (DRC). Therefore, the study was examined the productivity gap and the comparative advantage of producing BADC hybrid Boro seed. Primary data were collected from 240 adopters and 240 non-adopters of BADC Boro seed from eight districts of Bangladesh. The average productivity of adopters and non-adopters of BADC Boro seed was 5274 and 4885 kg ha-1, respectively. The average productivity gap between adopters and non-adopters was positive (389 kg ha-1). The average productivity of adopters was 1.08 times higher than that of non-adopters. The study pointed out that 9.51% productivity gap was identified due to the difference in observable characteristics and 90.49% gap to the difference in the yields of such characteristics. The DRC of hybrid Boro seed was 0.87 which is implying that BADC has a comparative advantage in producing hybrid Boro seed. The study revealed that an adequate supply of BADC Boro seed to the farmers will enhance Boro rice productivity in Bangladesh. Therefore, BADC should take necessary steps to increase hybrid Boro seed production to decrease imports and save foreign currency of Bangladesh. SAARC J. Agric., 21(1): 115-126 (2023)